Modelo discreto para avaliação dos esforços e momentos máximos de silos de armazenamento em condição de carga/descarga: uma análise exploratória - Pereira, Henrique de Oliveira (2022)
Brazil is one of the largest grain producers in the world, with an annual production of 255 tons of grains, making the demand for storage of these grains high. The type of structure most used for storage are metallic cylindrical silos, being slender shell structures, which have a great capacity to resist axial loads and lateral pressures that are submitted by grain storage. This study aims to analyze the behavior of orthotropic and longitudinally stiffened silos subjected to static and dynamic actions. For mathematical modeling of the orthotropic silo, the nonlinear Sanders- Koiter theory is used and the grain pressures under the silo walls are defined according to the Janssen model. Discretized equations of motion for the cantilever-free silo are obtained by applying Hamilton’s Principle and the Rayleigh-Ritz method. First, the results obtained for the maximum displacements and natural frequency by the analytical model are compared with those determined from a numerical analysis via finite elements. This first step, in addition to validating the proposed analytical formulation, allows determining the number of degrees of freedom necessary to obtain a reliable analytical model for the other parametric analyzes of this work. Then, the increase of the internal forces and moments that arise in the silo during the grain charging/discharging process for different geometries, physical properties and distance between the longitudinal stiffeners are evaluated. From the results found in this work, we propose factors to increase the static effects for an orthotropic, cantilever-free and longitudinally stiffened silo, in order to simplify the initial design phases without disregarding the importance of the dynamic effects that arise due to the grain charging/discharging process.